Educational and Social Exergaming: A Perspective on Physical, Social, and Educational Benefits and Pitfalls of Exergaming at Home During the COVID-19 Pandemic and Afterwards - Rüth, Marco; Kaspar, Kai (Frontiers in Psychology, 2021)
Physical inactivity and COVID-19 signify two pandemics with negative physical, mental, and economic consequences. Younger and older people have not reached the recommended physical activity level for years. Societal restrictions due to COVID-19 additionally reduce opportunities for physical activity and they increase social isolation. Here, we outline how playing exergames with others (social exergaming) at home could foster physical and mental health and promote communication and discussions on exergaming. Accordingly, we highlight the educational and social benefits of exergaming at home and delineate the concept of Educational and Social Exergaming (EASE). We outline specific benefits and pitfalls of exergaming regarding its physical and non-physical effects, including educational values of discussing exergaming experiences and related topics. Moreover, we discuss the relevance of practical guidelines for educational and social exergaming at home as well as prospects for future research. Overall, educational and social exergaming could alleviate several detrimental effects of both pandemics on the health and well-being of people of all ages.